Effects of Parameter Variations Generated by Pumping on LNAPL Migration in the Aquitard: An Analytical and Experimental Study - Yue Su; Yong Huang; Huan Shen; Xiaosong Dong; Xiaochang Sun; Zhimin Fu (Toxics)
The parameter variations in the aquitard have an important influence on the migration laws of contaminants in the aquitard. In order to study the influence of dynamic changes in parameters during pumping on the migration laws of Light Non-aqueous Phase Liquid (LNAPL) in the aquitard, the one-dimensional consolidation and groundwater flow equations for the aquitard were employed to derive the governing equations for the migration of LNAPL in the aquitard. A self-designed experimental platform was developed to investigate the effects of the pore water pressure, consolidation deformation, and pumping rate on LNAPL migration during pumping. The laboratory experimental results indicated that during pumping, the migration behavior of LNAPL in the aquitard typically exhibited a trend toward the pumping well and the overlying aquifer. The closer to the pumping well, the greater the change in the pore water pressure, the greater the amount of consolidation deformation, the earlier the state of densification, and the slower the migration rate of LNAPL in the aquitard. The nearer to the bottom of the aquitard, the larger the amount of consolidation deformation in the aquitard and the slower the migration rate of LNAPL in the aquitard. Also, the pumping rate had an important influence on groundwater flow movement and contaminant migration. The characteristics of parameter variations in the aquitard and laws of LNAPL migration during pumping were systematically studied and analyzed; these research results can provide a reference for the prediction and remediation of LNAPL in contaminated sites.